Distribution and bioprospecting potential of actinobacteria from Indian mangrove ecosystems - Manikkam, Radhakrishnan; Pati, Premalata; Thangavel, Shanmugasundaram; Venugopal, Gopikrishnan; Joseph, Jerrine; Ramasamy, Balagurunathan; Dastager, Syed G. (Microbial Diversity in Ecosystem Sustainability and Biotechnological Applications, 2019)
Actinobacteria are the ecologically and economically important prokaryotes with the unprecedented ability to produce novel metabolites. They are widely distributed in nature due to their physiological and metabolic versatility. Actinobacteria from marine ecosystem are recognized as a promising source for novel bioactive metabolites. Notably, mangroves are the most fertile and productive marine ecosystem due to their ecophysiological conditions and vast microbial diversity. At the global level, there are many novel actinobacteria which have been reported from mangrove ecosystems and also explored for their bioprospecting potential. However, in India, microbiologists have explored actinobacteria from selected mangrove ecosystems for the past five decades with special reference to culturable diversity and antimicrobial, antimycobacterial, anticancer, and enzymatic activities. So far, around 22 rare actinobacterial genera have been reported from the Indian mangrove ecosystems. However, several other novel actinobacteria with promising bioprospecting potential are yet to be explored. Hence, research on actinobacteria in the Indian mangrove ecosystem is still in its infancy. This chapter will describe the exploratory research work carried out on the importance, diversity, antimicrobial and enzymatic activity, biodegradation, and nanotechnological potency of actinobacteria from the Indian mangrove ecosystems. This chapter will enable researchers to identify the gaps to be bridged for further research on Indian mangrove actinobacteria and exploit their potential to the maximum benefit to mankind.

Integrated genomic and functional analysis of Streptomyces sp. UP1A-1 for bacterial wilt control and solanaceae yield increase - Kaari, Manigundan; Manikkam, Radhakrishnan; Joseph, Jerrine; Krishnan, Sakthivel; Annamalai, Kishore Kumar; Khan, Abujunaid; Rajput, Vinay; Dastager, Syed Gulam; Dharne, Mahesh S.; Umar, Md; Venugopal, Gopikrishnan; Alexander, Balamurugan (Gene Reports, 2024)
<em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Ralstonia solanacearum<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> is one of the most destructive soil-borne pathogen, causing bacterial wilt to the solanaceae vegetables. <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 isolated from healthy solanaceae rhizosphere soil, exhibited the lowest disease incidence and increased fruit yield of solanaceae vegetables. However, the genomic and functional properties of UP1A-1 are unclear. Therefore, we conducted the present study to elucidate the genomic characteristics of UP1A-1 by whole genome sequencing. The results indicate that the genome of <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 consists of 8,252,902 bp and contains 72.42 % G + C. We identified the genes that confer plant growth promoting (PGP) function, which include those involved in siderophore production, indole-3-acetic acid biosynthesis, phosphate solubilization, nitrogen metabolism, and potassium metabolism. We also identified several other genes, such as chitinase, peroxidase, superoxide dismutase, catalase, proline biosynthesis, and glucose dehydrogenase, which are believed to be involved in the control of wilt disease. These genes revealed that the strain UP1A-1 has physiologically adapted to varied environmental conditions and could potentially control both abiotic and biotic stresses.